Perceived impact of a one-week journalology training course on scientific reporting competencies: prospective survey - Charles Phillipe de Lucena Alves; João de Deus Barreto Segundo; Marina Christ Franco; Rafael Ratto de Moraes; David Moher; Maximiliano Sérgio Cenci; Tatiana Pereira-Cenci; Anelise Fernandes Montagner (Journal of Evidence-Based Healthcare)
INTRODUCTION: The debate on scientific research and reporting integrity issues in Brazil is incipient. Literature suggests that a journalology training course could help to improve the competencies of the participants. OBJECTIVE: To evaluate the immediate impact of a journalology training course on perceived academic competencies, comprised of knowledge, attitudes, and skills.  METHODS: The course was taught in 5 consecutive days to an online audience of individuals from the health sciences. A self-applied questionnaire was employed before and immediately after the course, which included initial and acquired perceived knowledge, attitudes, skills. The Wilcoxon non-parametric test for paired samples was used for analysis.  RESULTS: A total of 45 individuals participated in the course, with a 53% response rate before and after. The number of participants in each course session ranged between 32 and 45. There was an improvement in perceived knowledge of: (1) writing review articles; (2) ethical aspects of research; (3) scientific authorship; (4) predatory practices; (5) publication bias and spin, and (6) researcher evaluation. There was no improvement in self-reported attitudes towards any item. There was an improvement in the perception of skills relating to: (1) writing a response letter and (2) writing an opinion as a reviewer. CONCLUSIONS: Overall, attendees who participated in the survey reported perceived improved knowledge and skills in some items but not in their attitudes. Therefore, the course appears to have been unable to modify perceived scientific reporting competencies.